1983
DOI: 10.1002/j.1552-4604.1983.tb02720.x
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Kinetics and Bioavailability After Single Intravenous and Oral Doses in Normal Subjects

Abstract: Nifedipine kinetics have not been described in clinically relevant detail because of difficulties in formulating a stable preparation for intravenous use and lack of a specific and sensitive assay for plasma nifedipine. We recently developed a gas-chromatographic method and determined conditions in which nifedipine could be protected from photodegradation. Therefore, we evaluated the kinetics and bioavailability of nifedipine in 12 normal subjects after single intravenous (1 mg/5 min) and oral (10 mg) doses. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(73 citation statements)
references
References 8 publications
5
67
1
Order By: Relevance
“…The authors concluded that calculation of the plasma ratio may provide a clue to the metabolic origin of the polymorphism in nifedipine disposition and a convenient procedure for phenotyping individuals. The very high AUC values for nifedipine in the seven normal subjects are at variance with the data in this paper and, after adjustment for dose, are about double those reported by Kleinbloesem et al, (1984a) and in other studies in normal young volunteers (Foster et al, 1983;Waller et al, 1984;Challenor et al, 1986Challenor et al, , 1987aLobo et al, 1986;. In addition, the AUC for nifedipine and the nifedipine to metabolite ratio for the unusual subject in the study of Schmid et al (1986) were about twice the maximum values found in the present population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The authors concluded that calculation of the plasma ratio may provide a clue to the metabolic origin of the polymorphism in nifedipine disposition and a convenient procedure for phenotyping individuals. The very high AUC values for nifedipine in the seven normal subjects are at variance with the data in this paper and, after adjustment for dose, are about double those reported by Kleinbloesem et al, (1984a) and in other studies in normal young volunteers (Foster et al, 1983;Waller et al, 1984;Challenor et al, 1986Challenor et al, , 1987aLobo et al, 1986;. In addition, the AUC for nifedipine and the nifedipine to metabolite ratio for the unusual subject in the study of Schmid et al (1986) were about twice the maximum values found in the present population.…”
Section: Discussionsupporting
confidence: 83%
“…Nifedipine is a dihydropyridine calcium channel blocker which undergoes extensive first pass metabolism in man following oral administration (Foster et al, 1983;Waller et al, 1984). Metabolism is apparently via a single pathway involving initial oxidation to the pyridine analogue, followed by conversion to acid metabolites which are excreted in the urine (Horster et al, 1972; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also reported a very marked scatter in individual plasma levels during the absorption phase, but did not provide any k a data [5,14]. The authors of the latter study attributed this variability to differences in gastrointestinal absorption and/or hepatic first pass extraction and metabolism.…”
Section: Ethnic Differences and Other Nifedipine Pharmacokineticsmentioning
confidence: 83%
“…[1] There are numerous publications on the bioavailability and pharmacokinetics of nifedipine [1][2][3] but no work on the pharmacokinetics of nifedipine in the Pakistani population has been reported previously, to the best of our knowledge. Such a study would be important since it should provide useful information on drug blood levels and metabolic status [4][5][6][7] which could influence the use of this drug among Pakistanis. Furthermore, some dosage adjustments may be needed, based on pharmacokinetic data, for patients in this region of the world [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the in vivo measurement of calcium antagonist receptor occupation may offer a better insight into the interaction at receptor level by calcium antagonists and into the elucidation of tissue selectivity of these drugs under physiological conditions. Some 1,4-DHP derivatives are subject to extensive and variable first pass metabolism by the liver (Higuchi & Shiobara, 1980;Foster et al, 1983) which reduces systemic bioavailability and drug efficacy after oral administration. The relationship between the cardiovascular effects of some 1,4-DHP derivative calcium antagonists and their plasma concentrations in experimental animals and in man has been investigated (Takata & Kato, 1986, Graefe et al, 1988, Wu et al, 1988.…”
Section: Discussionmentioning
confidence: 99%